Impact of continuous glucose monitoring in youth with type 1 diabetes aged 15–21 years. Issue 2 (31st May 2022) - Lee, Myron Andrew; Holmes‐Walker, Deborah Jane; Farrell, Kaye; Clark‐Luccitti, Ashley
Abstract: Background: People with type 1 diabetes (T1D) aged <21 years are eligible for subsidised continuous glucose monitoring (CGM) products under the Australian National Diabetes Services Scheme. There are few real‐world published studies to evaluate the benefits of CGM in young adults. Aims: To perform a real‐world observation study among youth with T1D to evaluate CGM use and benefits of CGM. Methods: Patients at the Westmead Hospital Young Adult Diabetes Clinic aged 15–21 years who commenced CGM before July 2018 were followed for 6 months post commencement of CGM. Differences in HbA1c and glucose metrics at baseline and follow up are compared between those commencing CGM and those that did not. Results: Forty‐four (38%) of 115 eligible patients commenced CGM. Demographic characteristics and baseline HbA1c did not differ significantly between those started on CGM and those that did not. At 6 months, 18 (41%) of 44 patients still used CGM, with discomfort and inconvenience the most common reasons for dropout. In CGM continuers, at 6 months compared with baseline, there was no change in HbA1c (8.2% vs 8.0%; P = 0.8), coefficient of variation of glucose (38% vs 39%; P = 0.5) or percentage time in range (52% vs 58%; P = 0.3). Six‐month follow‐up HbA1c in CGM non‐users deteriorated significantly compared with users. Mean hypoglycaemia fear scores (worry scale) were significantly decreased from baseline at 6 months (33 vs 18; P < 0.01). Conclusion: There are high rates of discontinuation in CGM use among youth with T1D. At 6 months of CGM use, there was no significant change in glycaemic control, although HbA1c in non‐users deteriorated significantly. Worry of hypoglycaemia was significantly decreased among those who continued CGM.